High frequency dielectric materials for medicine and telecommunications. (1st October 2021) - Lanagan, Michael T.; Brown, Tucker; Perini, Steve; Yang, Qing X.
Abstract: The MHz–THz frequency range encompasses several important applications including magnetic resonance imaging (MRI) and wireless communications ferroelectric and paraelectric materials with high permittivity values have been applied to increase the sensitivity of MRI operating between 50 and 500 MHz. Low relative permittivity materials ( ε r  < 5) with low dielectric loss are becoming more important for 5G applications above 6 GHz with an emphasis on low dielectric loss.